THE CORRELATION BETWEEN THE HABIT OF WATCHING ENGLISH YOUTUBE VIDEOS AND STUDENTS’ VOCABULARY MASTERY IN EFL CLASS - Sri Yulianti B; Maemuna Muhayyang; Munir Munir (JTechLP: Journal of Technology in Language Pedagogy, 2022)
This research was aimed to know the students’ habit on watching English videos on YouTube, the students’ vocabulary mastery, and the correlation between the habit of watching English YouTube videos and students’ vocabulary mastery in EFL class. The study applied a correlational research design. The population of this research was the second grade of SMA Negeri 3 Takalar taking 36 students as a sample by using cluster random sampling technique. The instrument of this research was questionnaire to know students’ habit in watching English YouTube videos and vocabulary test to know the students’ vocabulary mastery. The result of this research indicates that: (1) the students’ habit at the second grade of SMA Negeri 3 Takalar is in often category, (2) the students’ vocabulary mastery is classified in good classification, and (3) the correlation between the habit of watching English YouTube videos and students’ vocabulary mastery was positive because r calculation = 0.895 was high than value of r table = 0.329, which means that the H0 of this research was rejected and H1 was accepted. Therefore, it can be concluded that there was any significant correlation between the habit of watching English YouTube videos and students’ vocabulary mastery.